The Interdisciplinarity of Misogyny, Misandry and Misanthropy Gender Variations Corpus Analysis of Orwell’s 1984 - Majetic, Senka (Eximia, 2023)
The article "Misogyny, Misandry and Misanthropy Gender Variations Corpus Analysis in Orwell’s 1984" explores the problem immensely present in Society. Corpus analysis is a confirmation of the hypothesized problem. The article is a marker of systematic Misogyny, Misandry and Misanthropy. The need for personal freedom protection is identified and discussed. The problem presented in Orwell’s 1984 is the hypothesis of the current state of society and motivation for a "current society" case study, the need for a "gender revisitation". Gender Variations are shown as Misogyny, Misandry and Misanthropy. Gender Variations, interdisciplinary studies trend is the corpus itself presenting Misogyny, Misandry and Misanthropy diversification, not as male, female and humankind unity. Multidisciplinarity is achieved through chosen interdisciplinarity of Language, Gender and Literature via Corpus Linguistics and Statistics. A corpus test sample has been used.